Frequency dependence and assembly characteristics of silver nanomaterials trapped by dielectrophoresis. (September 2015) - Kataoka, R; Tokita, H; Uchida, S; Sano, R; Nishikawa, H
Abstract: For rapid and accurate fabrication of industrial products, the development of effective technique to manipulate and assemble nanomaterials is essential. In the present work, we investigated the dielectrophoretic behavior of silver nanoparticles and nanowires at various driving frequencies and voltage amplitudes, and examined three-dimensional assembly of the nanomaterials using dielectrophoretic devices with microstructures. The collectable range in frequency for nanoparticles and nanowires was from 10 kHz to 1 MHz. In particular, the aggregation shape of nanowires was changed against driving frequency. The bunch of nanowires was bridged between pillars of dielectrophoretic device. When the applied voltage was turned off, the trapped nanowires were entirely released. In pit type device, trapping of nanoparticles was observed in outermost pits of array. The aggregates of nanoparticles were directly fixed to the bottom electrode.